KEDUDUKAN MAHRAM DALAM HUKUM PERKAWINAN ISLAM: ANTARA TRADISI DANKEBUTUHAN KONTEMPORER - Deni Afriansyah; Nia amira; Arya Farhan Azizi S; Zakaria Ahmad Mrp; Fera Aisah Bancin; Iwan Iwan (CV. ALIM'SPUBLISHING, 2025)
The position of the mahram in Islamic marriage law is an important aspect that regulates who can be married and who cannot. Mahrams are divided into two categories: mahram mu'abbad and mahram ghairu mu'abbad. Initially, this law was based on tradition and nasab, but in the contemporary context, the understanding of mahram needs to be adapted to societal developments and practical needs without ignoring sharia principles. This journal will analyze the position of the mahram in Islamic marriage law, between tradition and contemporary needs.